2021
DOI: 10.1186/s12964-021-00749-4
|View full text |Cite
|
Sign up to set email alerts
|

PIM kinases inhibit AMPK activation and promote tumorigenicity by phosphorylating LKB1

Abstract: Background The oncogenic PIM kinases and the tumor-suppressive LKB1 kinase have both been implicated in the regulation of cell growth and metabolism, albeit in opposite directions. Here we investigated whether these kinases interact with each other to influence AMPK activation and tumorigenic growth of prostate and breast cancer cells. Methods We first determined how PIM and LKB1 kinases affect AMPK phosphorylation levels. We then used in vitro kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…This effect may be associated with the AMPK inhibition by TDRD7 , identified by Subramanian et al ( 15 , 16 ). PIM1 has been identified to block AMPK activation ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…This effect may be associated with the AMPK inhibition by TDRD7 , identified by Subramanian et al ( 15 , 16 ). PIM1 has been identified to block AMPK activation ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of PIM2 reduced protein expression of Osterix to prevent bone loss in myeloma 20) . Moreover, PIM2 functioned as a negative regulator of liver kinase B1 to reduce the activity of AMPK through decreasing AMPK phosphorylation at Thr 172 29) and increasing AMPK phosphorylation at Thr 467 18) . Our results demonstrated that protein expression of CO-L1A1, OPN and RUNX2 in lipopolysaccharide-treated PDLCs were increased by knockdown of PIM2, and silence of PIM2 increased phosphorylation of AMPK at Thr 172 in lipopolysaccharide-treated PDLCs.…”
Section: Discussionmentioning
confidence: 99%
“…FuGENEÒ HD Transfection Reagent (Promega, Madison, WI, USA) was used for plasmid transfections according to the manufacturer's protocol. The use of CRISPR/Cas9-based genome editing to prepare knock-out derivatives of MCF7 and PC3 cells lacking all three members in the PIM family has previously been described [13]. Eukaryotic and bacterial vectors pcDNA TM 3.1/V5-His-C and pGEX-6P-1 for expression of wild-type (WT) human PIM kinases have been described previously [10].…”
Section: Methodsmentioning
confidence: 99%
“…PIM kinases are a family of serine-threonine kinases with three highly homologous family members (PIM1, PIM2 and PIM3) that are often over-expressed in haematological or solid tumours [1][2][3] and that contribute to tumorigenesis there [4][5][6]. The PIM kinases are constitutively active [7] and regulate cell survival, motility, proliferation and metabolism by phosphorylating a wide range of substrates including BAD [8], NFATC1 [9], NOTCH1 [10], NOTCH3 [11], CAPZ [12] and LKB1 [13]. Knocking out all three members of the PIM family results in LKB1-dependent AMPK activation [13,14], increased production of reactive oxygen species as well as altered expression of several metabolic enzymes involved in glycolysis, pentose phosphate pathway or oxidative phosphorylation [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation